The Role of Human Resource Quality, Discipline, and Motivation in Employee Performance PT. PLN Indonesia Power Generating Business Unit Asam-Asam Kalimantan - Rizal, Ahmad; Sriyono,; Supardi, (Jurnal Manajemen, 2025)
Employee performance is a key factor in determining the success of an organization, especially in the energy sector which has high demands for efficiency and innovation. In the context of PT. PLN Indonesia Power Generating Business Unit Asam-Asam Kalimantan, employee performance is an important element to ensure operational reliability and support national energy needs. The purpose of this study is to examine the role of human resource quality, discipline, and motivation on employee performance in this business unit. The study was conducted using a quantitative method with a questionnaire-based survey compiled on a Likert scale that will be distributed or shared with respondents. The study population was 181 people covering all employees, while the sample in this study included all employees of PT. PLN Indonesia Power Generating Business Unit Asam-Asam Kalimantan with data analysis carried out using multiple linear regression. The results of this study indicate that human resource quality has a significant effect through relevant competencies to support strategic goals. Work discipline creates order and efficiency, while motivation, both intrinsic and extrinsic, is the main driver of employee productivity and engagement. The integration of these three factors significantly improves employee performance. However, a balance is needed, because excessive emphasis on discipline can hinder creativity. A holistic management approach is recommended to achieve optimal performance and organizational sustainability.